2020
DOI: 10.1007/s40195-020-00998-1
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure and Mechanical Performance of Ti–6Al–4V Lattice Structures Manufactured via Electron Beam Melting (EBM): A Review

Abstract: Electron beam melting (EBM) process is an additive manufacturing process largely used to produce complex metallic components made of high-performance materials for aerospace and medical applications. Especially, lattice structures made by Ti-6Al-4V have represented a hot topic for the industrial sectors because of having a great potential to combine lower weights and higher performances that can also be tailored by subsequent heat treatments. However, the little knowledge about the mechanical behaviour of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
44
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 98 publications
(46 citation statements)
references
References 81 publications
2
44
0
Order By: Relevance
“…Studies have compared the powder recyclability in EBM and LPBF and found that they are rather similar [69][70][71]. In contrast to LPBF, a vacuum atmosphere (around 1 × 10 -5 mbar) is applied in the EBM chamber, which is useful to avoid any contamination, especially for the processing of reactive materials such as titanium alloys or gamma titanium aluminide intermetallics [72]. Moreover, since EBM employs a different source of energies, compared to the one used in LPBF, higher scanning rates and generally preheating of the powder (even up to 1100 °C) is possible.…”
Section: Electron Beam Meltingmentioning
confidence: 99%
“…Studies have compared the powder recyclability in EBM and LPBF and found that they are rather similar [69][70][71]. In contrast to LPBF, a vacuum atmosphere (around 1 × 10 -5 mbar) is applied in the EBM chamber, which is useful to avoid any contamination, especially for the processing of reactive materials such as titanium alloys or gamma titanium aluminide intermetallics [72]. Moreover, since EBM employs a different source of energies, compared to the one used in LPBF, higher scanning rates and generally preheating of the powder (even up to 1100 °C) is possible.…”
Section: Electron Beam Meltingmentioning
confidence: 99%
“…Flexible design technique: The outstanding feature of the AM process is that it applies the layer by layer manufacturing method, which can create almost any complex geometry [17]. The layer by layer deposition strategy is in contrast to subtraction due to its limitation in design flexibility such as the need for fixtures, different tooling, possible collisions in the manufacture of complex geometry, and the difficulty of tool access to more profound and invisible areas [24].…”
Section: Chapter Literature Review 21 Additive Manufacturingmentioning
confidence: 99%
“…In powder bed systems, a layer of powder is spread on the building platform or on the previously solidified layer and is selectively fused via an energy source that can be either electron beam or laser beam [6][7][8]. The ability to produce high-resolution features and internal channels, as well as precision dimensional control, are considered the main advantages of powder bed AM processes [5,9,10]. In contrast, in powder/wire feed systems, the material is fed directly inside a melt pool which is already formed by a focalized heat source on the substrate or on the already deposited layer.…”
Section: Introductionmentioning
confidence: 99%